2000
DOI: 10.1001/archinte.160.18.2855
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review of Clinical Prediction Rules for Neuroimaging in the Evaluation of Dementia

Abstract: Background: Clinical practice guidelines for dementia do not recommend routine neuroimaging but vary in their recommended clinical prediction rules to identify patients who should undergo neuroimaging for potentially reversible causes of dementia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
3

Year Published

2001
2001
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(14 citation statements)
references
References 34 publications
(60 reference statements)
0
11
0
3
Order By: Relevance
“…Gifford et al have recently reviewed studies on the ability of rules for clinical prediction to lead to the suspicion of reversible causes of dementia and to determine who should undergo CT or MRI 1. The authors, as well as others,19 found that the most accurate prediction rule was that of Dietch,20 requiring imaging in patients with recent onset (less than 1 month) of cognitive symptoms, fluctuations or acute changes (within 48 hours) of cognitive function, focal signs or symptoms, papilloedema or visual field deficits, headache, history of recent head trauma or malignant tumour, seizures, history of stroke, urinary incontinence, or gait ataxia or apraxia.…”
Section: Reversible or Treatable Intracranial Causes Of Cognitive Impmentioning
confidence: 99%
See 1 more Smart Citation
“…Gifford et al have recently reviewed studies on the ability of rules for clinical prediction to lead to the suspicion of reversible causes of dementia and to determine who should undergo CT or MRI 1. The authors, as well as others,19 found that the most accurate prediction rule was that of Dietch,20 requiring imaging in patients with recent onset (less than 1 month) of cognitive symptoms, fluctuations or acute changes (within 48 hours) of cognitive function, focal signs or symptoms, papilloedema or visual field deficits, headache, history of recent head trauma or malignant tumour, seizures, history of stroke, urinary incontinence, or gait ataxia or apraxia.…”
Section: Reversible or Treatable Intracranial Causes Of Cognitive Impmentioning
confidence: 99%
“…The authors, as well as others,19 found that the most accurate prediction rule was that of Dietch,20 requiring imaging in patients with recent onset (less than 1 month) of cognitive symptoms, fluctuations or acute changes (within 48 hours) of cognitive function, focal signs or symptoms, papilloedema or visual field deficits, headache, history of recent head trauma or malignant tumour, seizures, history of stroke, urinary incontinence, or gait ataxia or apraxia. However, even Dietch's rule could not attain 100% sensitivity1—the benchmark figure that most clinical neurologists and psychiatrists consider acceptable in the detection of reversible causes 16. The bottom line is that, although the vast majority of scans carried out in patients with cognitive deterioration are negative, no combination of first line (clinical and laboratory) signs can identify cases of reversible or treatable causes with 100% sensitivity and reasonably high specificity 17…”
Section: Reversible or Treatable Intracranial Causes Of Cognitive Impmentioning
confidence: 99%
“…5 The yield for this purpose varies between 1 and 10% and may be even lower. 6,7 However, Gifford et al 8 showed that the there is considerable uncertainty in the evidence behind clinical prediction rules to identify which patients with dementia should undergo neuroimaging, and the application of these rules may miss patients with potentially reversible conditions, hence it is widely accepted that a structural imaging procedure should be performed routinely in each patient with suspected dementia. 8 …”
Section: Discussionmentioning
confidence: 99%
“…While the prevalence of such pathology is low, it is very difficult to predict prior to scanning which patients will have organic brain lesions. A review of the published clinical prediction rules (Gifford et al, 2000) revealed that none of the published recommendations have a consistently high sensitivity and specificity. The clinical prediction rule proposed by Dietch (1983) suggests a series of 11 criteria for identifying patients unlikely to benefit from cranial CT (Table 1).…”
Section: Discussionmentioning
confidence: 99%